Adrenocortical Causes of Hypertension. (19th January 2011) - Moraitis, Andreas; Stratakis, Constantine
Abstract : Primary aldosteronism is the most common cause of secondary hypertension. In the past, screening for primary aldosteronism was offered only in patients with hypertension associated with hypokalemia. Recent studies showed that hypokalemia is seen in only 25% of the patients with primary aldosteronism, which has increased the prevalence of primary aldosteronism to 10–15% of all cases with new onset hypertension.